Selective elimination of senescent cells by mitochondrial targeting is regulated by ANT2 - Hubackova, Sona; Davidova, Eliska; Rohlenova, Katerina; Stursa, Jan; Werner, Lukas; Andera, Ladislav; Dong, LanFeng; Terp, Mikkel G; Hodny, Zdenek; Ditzel, Henrik J; Rohlena, Jakub; Neuzil, Jiri (Cell death and differentiation, 2019)
Cellular senescence is a form of cell cycle arrest that limits the proliferative potential of cells, including tumour cells. However, inability of immune cells to subsequently eliminate senescent cells from the organism may lead to tissue damage, inflammation, enhanced carcinogenesis and development of age-related diseases. We found that the anticancer agent mitochondria-targeted tamoxifen (MitoTam), unlike conventional anticancer agents, kills cancer cells without inducing senescence in vitro and in vivo. Surprisingly, it also selectively eliminates both malignant and non-cancerous senescent cells. In naturally aged mice treated with MitoTam for 4 weeks, we observed a significant decrease of senescence markers in all tested organs compared to non-treated animals. Mechanistically, we found that the susceptibility of senescent cells to MitoTam is linked to a very low expression level of adenine nucleotide translocase-2 (ANT2), inherent to the senescent phenotype. Restoration of ANT2 in senescent cells resulted in resistance to MitoTam, while its downregulation in non-senescent cells promoted their MitoTam-triggered elimination. Our study documents a novel, translationally intriguing role for an anticancer agent targeting mitochondria, that may result in a new strategy for the treatment of age-related diseases and senescence-associated pathologies.
Keywords: stárnutí buněk; Mice, SCID; viabilita buněk; Cell Proliferation; Animals; genový knockdown; myši inbrední NOD; Mice, Transgenic; Humans; Mice; Antineoplastic Agents, Hormonal; mitochondrie; xenogenní modely - testy protinádorové aktivity; Xenograft Model Antitumor Assays; Adenine Nucleotide Translocator 2; hormonální protinádorové látky; Mitochondria; MFC-7 buňky; proliferace buněk; Tamoxifen; translokátor adeninových nukleotidů 2; myši transgenní; zvířata; apoptóza; Mice, Inbred NOD; tamoxifen; MCF-7 Cells; transfekce; Gene Knockdown Techniques; Cell Survival; lidé; myši SCID; Cellular Senescence; Apoptosis; Transfection; myši